Bronchial epithelial cells of young and old mice directly regulate the differentiation of Th2 and Th17. Issue 2 (1st February 2019) - Liu, Da; He, Long; Ding, Ning; Sun, Wenjin; Qiu, Lulu; Xu, Li; Jia, Aijun; Peng, Cong; Zhang, Dongshan; Xiang, Xudong
Abstract : To determine whether or not house dust mite (HDM) and HDM+lipopolysaccharide (LPS) exposure causes a difference in T-cell subsets from young and old mice. The bronchial epithelial cells (BECs) from young and old mice were divided into three groups (PBS (control), HDM, and HDM+LPS). CD4 + naive T cells from the spleen and lymph nodes were collected after 24 h of co-culture with BECs. The number of Th2 and Th17 cells was elevated in the HDM and HDM+LPS groups compared with the control group; these responses were exacerbated when exposed to HDM+LPS. The number of HDM- and HDM+LPS-specific Th2/Th17 cells in young mice was higher than old mice; however, the Th2:Th17 cell ratio was greater in young mice, whereas the Th17:Th2 cell ratio was greater in old mice. The expression of GATA-3 and RORc was increased in the HDM+LPS and HDM groups compared with the PBS group and exhibited most in HDM+LPS group. The expression of HDM+LPS-specific GATA-3 in young mice was higher, while the expression of HDM+LPS-specific RORc in old mice was higher. Murine BECs directly regulated CD4 + naive T-cell differentiation under allergen exposure.